The project managers guide to IDIQ task order service contracts : how to win and perform on task order contracts (Palgrave Macmillan, 2017)
Every year the US federal government will spend roughly 100 billion dollars through competitive IDIQ (Indefinite Duration Indefinite Quantity) contracts. When you add in contracts awarded by State governments and commercial organizations using very similar processes you're looking at 700 billion dollars' worth of business. Getting a slice of that pie depends on how well you manage the contracting project. This is because IDIQs are essentially empty contract structures which then require a second round of winning task orders. For contracts with the government, this two-step structure which is specified in law and regulation, has specific pitfalls and opportunities which are rarely the subject of contract and project management training. Salesky's coaching style talks you through the specific challenges in the startup, management, and closing of the IDIQ. This book gives a pragmatic and best-practice description of the entire life cycle of this type of contract offering you the "inside advisor" you need to help you through the pragmatics issues of clients', performers', and bosses' expectations.
Keywords: Business.; New business enterprises.; Project management.; elektronické knihy; electronic books